Eksplorasi Etnomatematika Geometri Bangun Datar Segitiga pada Pakaian Tradisonal Sortopi Khas Suku Batak Toba - Elvi Mailani; Riska Sri Pratiwi Tambunan; Febri Deasari Simamora; Delima Situmorang; Karina Sitorus; Gnade Denalita Saragih; Nadia Grace Sianturi; Nur Rarastika (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Exploration of ethnomathematics in the context of flat geometry, especially triangles, in traditional Batak Toba clothing, is an interesting and important study. This study aims to reveal the relationship between mathematical concepts and local culture, and how geometric elements can be found in the design of Sortopi traditional clothing. This research method uses a qualitative approach with data sources, namely library studies, from several literature reviews according to the topic and purpose of the study. The results of the study show that Sortopi is a complement to traditional Batak clothing used by men as a crown or headband. The shape of Sortopi contains elements of isosceles triangle flat geometry, thus showing that cultural elements are inseparable from mathematics.